Italy : ensuring regulatory quality across levels of government - Konvitz, Josef W.; Organisation for Economic Co-operation and Development. Regulatory Policy Division (Paris : OECD, 2007)
In recent years Italy has moved towards greater devolution of regulatory powers at regional level, in a European context where this dimension becomes increasingly important. This review analyzes first the institutional set-up for multi-level regulation, the specifics of power sharing between the state and the regions, as well as the horizontal and vertical co-ordination mechanisms in place in the country, before turning to the use of policy instruments and regulatory tools in four Italian regions: Veneto, Calabria, Campania and Tuscany.--Publisher's description.
Multi-level regulatory governance in Italy -- Capacity to produce high quality regulation in Italian regions. Veneto -- Calabria -- Campania -- Tuscany -- Conclusions and policy recommendations.
Produced by the Regulatory Policy Division under Josef Konvitz
Includes bibliographical references
Keywords: Trade regulation -- Italy; Deregulation -- Italy; Industrial policy -- Italy